Convergence of #MeToo Movement into #SayaJuga?: How Social Activists in Malaysia Leverage Social Media in Empowering Women - Goh, Yong Le (UI Scholars Hub, 2022)
This research primarily aims to highlight the interconnections among social activists, social media, and ordinary public in the actor-network encompassing women empowerment in Malaysia. The secondary aim is to expand the knowledge gap on active social activists’ perspective toward the development of the country’s women empowerment. Qualitative interview was used to create a holistic research on interviewee’s personal involvement toward women empowerment in Malaysia. The following themes were derived from the data analysis: an association exists between women empowerment and #MeToo movement; communication barriers to popularizing women empowerment; vulnerable groups in search of gender equality; and opinions toward policymakers’ attitudes in Malaysia. Actor-network theory was employed in highlighting the roles of human and non-human actants in the communication network. It suggested whether a unified hashtag is required to discuss gender equality issues in Malaysia. This research also highlights the research gap of the contemporary viewpoint from the social activists who aimed to empower their audience in Malaysia. Results provide insights into how opinion leaders and policy makers should construct strategies toward reaching their intended audience.